2010
DOI: 10.1002/chem.200902882
|View full text |Cite
|
Sign up to set email alerts
|

Specific Induced Circular Dichroism and Enhanced B to Z Transitions of Duplexes Stabilized by Chromophore‐Linked Alkynylnucleoside Residues

Abstract: We have developed an induced circular dichroism (ICD) probe with a chromophore-linked alkynyldeoxyribose skeleton for analyzing higher-order structures of DNA duplexes in the visible-light region. When CG-repeated oligonucleotides (ODNs) with the probe at their 5' ends adopted Z-form duplexes at a high NaCl concentration, strong ICD signals were observed at the absorptive region of the chromophore. On the other hand, their B-form duplexes, formed at a low NaCl concentration, produced a faint ICD signal. The sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 118 publications
(184 reference statements)
0
7
0
Order By: Relevance
“…This effect was accompanied by changes in the CD spectra, which were used to follow the conformational change. The d(CG) 4 sequence with the porphyrin TAP at the 5′-end reached 50% conversion to Z-DNA at 0.75 M NaCl; however, full conversion was not achieved even at saturated conditions . For the unmodified sequence the concentration of NaCl for the midpoint transition was significantly higher, 2.6 M. Stabilization of an atypical DNA duplex was also observed for the d(GA) 4 sequence when TAP was placed at the 5′-end .…”
Section: Moieties Inserted At the 5′- Or 3′-end Of The Sequencementioning
confidence: 95%
See 1 more Smart Citation
“…This effect was accompanied by changes in the CD spectra, which were used to follow the conformational change. The d(CG) 4 sequence with the porphyrin TAP at the 5′-end reached 50% conversion to Z-DNA at 0.75 M NaCl; however, full conversion was not achieved even at saturated conditions . For the unmodified sequence the concentration of NaCl for the midpoint transition was significantly higher, 2.6 M. Stabilization of an atypical DNA duplex was also observed for the d(GA) 4 sequence when TAP was placed at the 5′-end .…”
Section: Moieties Inserted At the 5′- Or 3′-end Of The Sequencementioning
confidence: 95%
“…A fluorescein derivative, Et F (Figure C), at the 5′-end of the d(CG) 3 sequence was found to promote the B-to-Z transition to a larger extent than when it was placed at the 3′-end . Moreover, an induced CD signal in the chromophore region as a result of B-to-Z transition was detected only for the sequence with Et F at the 5′-end.…”
Section: Moieties Inserted At the 5′- Or 3′-end Of The Sequencementioning
confidence: 95%
“…A recent study revealed that the introduction of Et F (Fig. a) at the 5′‐end of the d(CG) 3 sequence promoted the B‐to‐Z transition . It has also recently been reported that a cubane‐like europium‐ l ‐aspartic‐acid complex (EuD) can convert B‐form DNA into Z‐form DNA under mimicked physiological conditions.…”
Section: Z‐dnamentioning
confidence: 99%
“…The duplex DNA generally adopts right‐handed helices under physiological conditions and may change to left‐handed helices depending on the sequence and medium conditions ( B – Z transition) . The B – Z transition is supposed to play a role in the gene expression pathway and is applied to a molecular switch of a nanodevice . A variety of ligand has been reported for the B – Z transition, the chiral recognition and the DNA template‐based asymmetric induction …”
Section: Figurementioning
confidence: 99%